An Improved Low-Complexity Decoding Algorithms for Non-Binary LDPC Codes in BeiDou Navigation System - Tan, Yumeng; Xi, Xiaoli; Yang, Hailong; Jiang, Ronghua (IOP conference series. Materials Science and Engineering, 2018)
The construction and development of BeiDou Navigation Satellite System (BDS) is divided into three parts: BDS-1, BDS-2, and BDS-3 in sequence. The Low-Density Parity-Check (LDPC) code is applied to the BDS-3 navigation system because of its proximity to Shannon limit and the low requirement of energy. Compared with other decoding algorithms, extended Min-Sum (EMS) algorithm has been applied in navigation because it can reduce the computation of check node (CN) and facilitate hardware implementation. However, our study indicates that by calculating the correct probability of the elements in the reliability matrix, the number of candidate elements can be further reduced, thus simplifying the update of the check nodes. In this paper, an improved extended Min-Sum (IEMS) decoding algorithms is used to BDS-3 LDPC codes. Compared with the traditional EMS algorithm, the proposed decoding algorithm has the advantages of less computation and higher decoding efficiency. To verify the complexity and performance of the IEMS, the complexity and Bit Error Rate (BER) of the proposed decoding algorithm in BeiDou are studied and discussed. The simulation results show that the number of CN operations in the IEMS algorithm is only 40% times as much as that of EMS. It indicates that the IEMS decoding algorithms can be a good candidate for BDS-3 LDPC codes.